Cover Feature: Adsorption of Acetate on Au(111): An in‐situ Scanning Tunnelling Microscopy Study and Implications on Formic Acid Electrooxidation (ChemPhysChem 22/2019). Issue 22 (11th November 2019) - Abdelrahman, Areeg; Hermann, Johannes M.; Jacob, Timo; Kibler, Ludwig A.
Abstract : The Cover Feature illustrates in‐situ scanning tunnelling microscopy of an Au(111) single crystal electrode in contact with acetic acid solution. Adsorbed acetate shows two different structures on Au(111) at the same potential, an initially incommensurate structure transforms into a thermodynamically more stable commensurate (2×2) structure (cover image: Areeg Abdelrahman). More information can be found in the Article by A. Abdelrahman et al. on page 2989 in Issue 22, 2019 (DOI: 10.1002/cphc.201900560 ).